The immunoregulation effect of tumor microenvironment in pancreatic ductal adenocarcinoma - Zhang, Jingchang; Li, Renfeng; Huang, Shuai (Frontiers in Oncology, 2022)
Pancreatic cancer has the seventh highest death rate of all cancers. The absence of any serious symptoms, coupled with a lack of early prognostic and diagnostic markers, makes the disease untreatable in most cases. This leads to a delay in diagnosis and the disease progresses so there is no cure. Only about 20% of cases are diagnosed early. Surgical removal is the preferred treatment for cancer, but chemotherapy is standard for advanced cancer, although patients can eventually develop drug resistance and serious side effects. Chemoresistance is multifactorial because of the interaction among pancreatic cancer cells, cancer stem cells, and the tumor microenvironment (TME). Nevertheless, more pancreatic cancer patients will benefit from precision treatment and targeted drugs. This review focuses on the immune-related components of TME and the interactions between tumor cells and TME during the development and progression of pancreatic cancer, including immunosuppression, tumor dormancy and escape. Finally, we discussed a variety of immune components-oriented immunotargeting drugs in TME from a clinical perspective.